Iconisation du discours et sémiotisation de l’évènement à travers la pancarte numérique - Kamila Oulebsir Oukil (Multilinguales)
This article deals with the digital sign as a study in its own right. It sheds light on this technogenre defined in the framework of the analysis of digital discourse (DNA) (Paveau 2017) which allows to represent an event and ensure its semioticization through the assembly text/image. The analysis of the corpus composed of signs relating to crisis situations allows us to observe how this verbo-iconic tool contributes to the definition of an iconization of enunciation and an iconization of discourse. The objective of this study is to show how meaning is constructed by the continuum between the iconic and the verbal at work in the digital sign.